Formulation of a novel soybean protein‐based wood adhesive with desired water resistance and technological applicability. Issue 27 (14th April 2016) - Fan, Bo; Zhang, LeiPeng; Gao, ZhenHua; Zhang, Yuehong; Shi, Junyou; Li, Jianzhang
ABSTRACT: A novel soybean protein‐based wood adhesive with good bond strength, excellent water resistance, and the desired technological applicability was formulated by combining thermal alkali degradation, thermal acid treatment, and crosslinking. The characterization results indicated that thermal alkali degradation could effectively improve the technological applicability, thermal acid treatment could positively improve the water resistance, and appropriate crosslinking modification could significantly enhance the bond strength and water resistance of the soybean protein adhesive. The crosslinker species, crosslinker level, and ratio of thermal alkali‐degraded soybean protein (DSP) to thermal acid‐treated soybean protein (TSP) had important effects on the primary properties of the soybean protein adhesives. The modified polyamide aqueous solution was the most preferable crosslinker because of its low viscosity, good crosslinking efficiency, and excellent miscibility with soybean protein solution. The optimal soybean protein adhesive that was formulated from 20 wt % modified polyamide as the crosslinker and a DSP/TSP ratio of 1:3 had a solid content of more than 35 wt %, suitable viscosity (∼2180 mPa s), a long work life (>16 h), good dry bond strength (2.94 MPa), and 28 h of boiling–dry–boiling cycled wet strength (1.29 MPa) that met the required values for structural use according to JIS K6806‐2003 commercial standards. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43586. Abstract :